2014
DOI: 10.1073/pnas.1415690111
|View full text |Cite
|
Sign up to set email alerts
|

JIP60-mediated, jasmonate- and senescence-induced molecular switch in translation toward stress and defense protein synthesis

Abstract: Two closely related genes encoding the jasmonate-induced protein 60 (JIP60) were identified in the barley genome. The gene on chromosome arm 4HL encodes the previously identified protein encoded by the cDNA X66376.1. This JIP60 protein is characterized here and shown to consist of two domains: an NH 2 -terminal domain related to ribosome-inactivating proteins and a COOH-terminal domain, which displays similarity to eukaryotic translation initiation factor 4E (eIF4E). JIP60 undergoes processing in vivo, as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 45 publications
0
42
0
2
Order By: Relevance
“…As described earlier, JIP60 is a 60 kDa jasmonate-inducible chimeric protein that consists of an N -terminal RIP domain and a C -terminal domain which displays similarity to eukaryotic translation initiation factor 4E [37,70]. Like maize RIP1, JIP60 differs from other RIPs in containing internal acidic peptides of 20–25 amino acids that will be removed during maturation of the protein.…”
Section: Biological Activity Of Cereal Rip Domainsmentioning
confidence: 99%
“…As described earlier, JIP60 is a 60 kDa jasmonate-inducible chimeric protein that consists of an N -terminal RIP domain and a C -terminal domain which displays similarity to eukaryotic translation initiation factor 4E [37,70]. Like maize RIP1, JIP60 differs from other RIPs in containing internal acidic peptides of 20–25 amino acids that will be removed during maturation of the protein.…”
Section: Biological Activity Of Cereal Rip Domainsmentioning
confidence: 99%
“…Therefore, any modifications in this fragment of 25S rRNA lead to the inactivation of the large ribosomal subunit and cessation of protein synthesis during the elongation step (Dunaeva et al 1999;Sawasaki et al 2008). JIP60 also plays a key role in inhibiting cytoplasmic protein synthesis via reversible ribosome dissociation into small and large subunits (Reinbothe et al 1994;Rustgi et al 2014). Some authors have suggested that the upregulation of JIP60 during salinity stress inhibits growth (Görschen et al 1995) and protects plants against stress.…”
Section: Signal Transduction Transcription and Translation Processingmentioning
confidence: 99%
“…One example is the JIP60 protein (60 kDa jasmonate-induced protein) found in barley (Chaudhry et al, 1994). This is a chimeric protein where a RIP domain is linked to a domain which has similarity to the eukaryotic translation initiation factor 4E (Rustgi et al, 2014).…”
Section: Ribosome-inactivating Proteinsmentioning
confidence: 99%